Análise comparativa e controlada entre os perfis moleculares imuno-histoquímicos do carcinoma mamário, da metástase gástrica de origem mamária e do adenocarcinoma gástrico primário - Jucá, Patrícia Chaves de Freitas Campos [UNIFESP] (2016)
Research bases: Breast cancer is the most frequent malignancy in the world, and many of these women develop distant metastases, most often to the bones, lymph nodes, lung, brain and liver. Metastases to the gastrointestinal tract are rare, but when present the stomach is the most common site. The differential diagnosis between gastric metastasis of mammary origin and primary gastric adenocarcinoma is difficult, and the radiological and endoscopic findings are similar and the morphological characteristics often do not allow the diagnosis of the cancer origin, hindering thus the proper treatment. Objective: The motivation and the goal of this research were to search the characterization of the molecular expression profile of markers in the primary site of breast carcinoma in gastric metastasis site and the second synchronous gastric primary or metachronous, in order to identify possible markers that facilitate the diagnosis of gastric metastases of mammary origin. Methods: The proposed research design was retrospective and controlled nature, making up three focus groups with 42 patients each, for a total of 126 patients; The Test group included patients with breast cancer who developed primary gastric adenocarcinoma (n=17) and metastatic mammary carcinoma in the stomach (n=25) diagnosed prior to treatment; the Control group I included patients diagnosed with primary breast carcinoma, without other associated lesions and the Control group II included patients with primary gastric adenocarcinoma, also without other associated lesions. The markers selected for analysis were: estrogen receptor (ER), progesterone receptor (PR), gross cystic disease fluid protein-15 (GCDFP-15) and hepatocyte nuclear factor 4-alpha (HNF4A), which were examined in tumor samples in 126 paraffin blocks, the Test and Controls groups I and II. The sensitivities, specific, accurate, prevalence, predictive values were calculated, estimating the test group the confidence intervals of values. Results: The tumor marker ER showed positive immunoreactivity in 12/25 patients (48.0%) with metastatic breast cancer in the stomach, sensitivity 48.0%, specificity of 100.0% and accuracy of 69.0%, with p<0.001; tumor marker PR showed positive immunoreactivity in 6/25 patients (24.0%) with metastatic breast cancer in the stomach, 24.0% sensitivity, specificity 100.0% and accuracy of 54.8%, with p<0.001; the GCDFP-15 marker showed positive immunoreactivity in 9/25 patients (36.0%) with metastatic breast cancer in the stomach, sensitivity 36.0%, specificity of 100.0% and accuracy of 61.9%, with p<0.001; tumor marker HNF4A showed positive immunoreactivity in 17/17 patients (100.0%) with primary gastric adenocarcinoma and negative in 1 patient with metastatic breast cancer in the stomach, 100.0% sensitivity, high specificity of 96.0% and accuracy of 97.6% with p value <0.001. Conclusion: Based on the results obtained in this research we can conclude that HNF4A, ER, PR and GCDFP-15 markers are effective in the differential diagnosis of primary gastric cancer and gastric metastasis of mammary origin. The marker HNF4A, in particular, can be regarded as highly significant to the exclusion of metastatic mammary carcinoma in the stomach, and thus can confer high power reliability in distinguishing these lesions.